Impact of European Union's Sanctions on External Economic Relations of Russia - Apostol, Marina (2024)
This thesis assesses the impact and costs of the EU’s sanctions in 2014 and 2022 on the Russian economy. Based on the studied literature and provided literature review, the research question of the thesis is aimed at the assessment of the economic impact of the EU’s sanctions in 2014 and 2022 on Russian trade and bilateral relations with key trade partners with a focus on trade flows in the oil industry. The hypothesis will test whether the EU’s sanctions imposed on Russia in 2014 and 2022 significantly and negatively impacted trade flows in the oil industry which resulted in lost trade for Russia and severe economic costs such as a decrease in GDP, decline in investment flows and bilateral trade volumes and negative development of the economic performance of companies involved. There are three chapters in the thesis. In the first chapter, the author defines what sanctions are, what sanctions’ impact means and formulate methodology and a research gap. In the second chapter, the author focuses on the assessment of the EU’s sanctions of 2014 and 2022 impact on the Russian economy from the internal, external balance, and trade balance points of view, including total trade, key trading partners, and two selected product groups- mineral fuels (SITC 3) and semiconductors (SITC 77637). In the third chapter, the author focuses on the assessment of the EU’s sanctions impact on the Russian oil industry and provides a case study of the selected Russian oil companies such as state-owned companies like Rosneft and Gazpromneft and private companies like Lukoil and Surgutneftgas. Based on the assessment provided, due to the EU's imposed sanctions the economic costs for Russia were major, not severe. The GDP declined more after 2014 than after 2022. The increase in GDP in 2022 was provoked by high global prices, but after the EU introduced the oil price cap, Russian GDP showed a decline in 2023.